Elastic behavior of binary and ternary refractory multi-principal-element alloys - Rui Feng; George Kim; Dunji Yu; Yan Chen; Wei Chen; Peter K. Liaw; Ke An (Materials & Design, 2022)
Elastic properties are essential to the mechanical performance of materials, and therefore, can be tuned to design high-performance materials. In this study, the elastic constants of the equiatomic ternary refractory multi-principal-element alloys, NbTiV, and MoNbV, were investigated, using in-situ neutron diffraction and first-principles calculations. The experimentally measured and theoretically predicted elastic constants show a good agreement. The alloying effect of adding Ti and Mo into NbV base alloy on the elastic constants is studied. Particularly, adding Ti elements into the NbV alloy results in the increase of the Zener anisotropy ratio from 0.59 to 0.99, leading to the formation of the elastically isotropic NbTiV alloy, while the addition of Mo decreases the anisotropy ratio to 0.52. Pugh’s ratio (B/G), Cauchy pressure (C12-C44), and Poisson’s ratio (ν) are used to predict the brittle/ductile nature of the studied alloys, which is consistent with the mechanical results. The present work provides valuable insights into the design of ductile and strong refractory high-entropy alloys by tuning the elastic properties.